Multiparty half-duplex systems and synchronous communications - Di Giusto, Cinzia; Germerie Guizouarn, Loïc; Lozes, Etienne (Journal of logical and algebraic methods in programming, 2023)
FIFO automata are finite state machines communicating through FIFO queues. They can be used, for instance, to model distributed protocols. Due to the unboundedness of the FIFO queues, several verification problems are undecidable for these systems. In order to model check such systems, one may look for decidable subclasses of FIFO systems. Binary half-duplex systems are systems of two FIFO automata exchanging over a half-duplex channel. They were studied by Cécé and Finkel who established the decidability in polynomial time of several properties. There is no obvious way to generalize the half-duplex property to multiparty systems. Cécé and Finkel proposed some generalizations but concluded that their notions of multiparty half-duplex systems were either too restrictive or too expressive. We explore in this paper other ways of generalizing half-duplex systems to multiparty. First, we introduce systems realizable with synchronous communications (RSC) and we show that RSC systems generalize half-duplex systems and retain the same good properties as binary half-duplex systems. Second, we introduce a notion of multiparty half-duplex systems that differs from the ones explored by Cécé and Finkel, and we show two results about this notion: (1) for mailbox communications, half-duplex systems are essentially the same as RSC systems, and (2) for peer-to-peer communications, the two notions are distinct, and RSC systems appear to be “the good one”, since peer-to-peer half-duplex systems are Turing powerful.